Hadith #3139 - Sunan Abi Dawud - Ali bin Sahl bin Qadim علي بن سهل بن قادم; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج (Sunan Abi Dawud)
He combined two persons from among the martyrs of Uhud in one garment.
Grade: Sahih

Hadith #4014 - Sunan Abi Dawud - Ali bin Sahl bin Qadim علي بن سهل بن قادم; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sat with us and my thigh was uncovered. He said: Do you not know that thigh is a private part ?
Grade: Sahih

Hadith #4549 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) addressed on the day of Conquest, or he said: On the conquest of Mecca on the ladder of the House or of the Ka’bah. Abu Dawud said: In a similar way of Ibn ‘Uyainah also transmitted it from ‘Ali b. Zaid, from al-Qasim b. Rab’iah, from Ibn ‘Umar, from the Prophet (ﷺ) ; and Ayyub al-Sukhtiyani transmitted it from al-Qasim b. Rabi’ah from ‘Abd Allah b. ‘Amr like the tradition of Khalid. Hammad b. Salamah also transmitted it from ‘Ali b. Zaid, from Ya
Grade: Da'if

Hadith #4551 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The bloodwit for unintentional murder which resembles intentional is twenty-five she camels which entered their fourth year, twenty five she-camels which had entered their fifth year, twenty five she-camels which had entered their third year, and twenty five camels which had entered their second year.
Grade: Da'if